INTRODUCTION OF PH.D THESIS BY DAO THI HA NINH “CHARACTERS ON POSITIONS AND DIRECTIONS IN MODERN CHINESE, AND THEIR VOCABULARY, GRAMMAR EQUIVALENTS IN VIETNAMESE” (Journal of Foreign Language Studies, 2024)
Bài viết giới thiệu luận án tiến sĩ của ĐÀO THỊ HÀ NINH  chuyên đề : “Phương vị từ tiếng Hán hiện đại và những biểu hiện từ vựng, ngữ pháp tương đương trong tiếng Việt“